Transitional and Long-Term Rehabilitation Care System After Stroke in Korea - Leigh, Ja-Ho; Kim, Won-Seok; Sohn, Dong-Gyun; Chang, Won Kee; Paik, Nam-Jong (Frontiers in Neurology, 2022)
Stroke is one of the leading causes of mortality and disability in Korea. Patients who experience stroke require adequate management throughout the acute to subacute and chronic stages. A large portion of patients with long-term functional issues require rehabilitative management even in the chronic stage. A comprehensive rehabilitation and care model for patients who experience stroke is necessary to effectively manage their needs during rehabilitation and allocate medical resources throughout the stages, thus ensuring reduced unmet needs and improved post-stroke quality of life. In Korea, the government and medical specialists are currently working to re-organize the rehabilitation care model including standardized triage and discharge planning after acute stroke treatment, and establishment of systematic transitional and long-term rehabilitation care plans. In this review, we briefly introduce the general rehabilitation triage after acute stroke and describe the current transitional and continuous care systems available for these patients in Korea. We also present the issues faced in transitional and long-term care plans of the current system and the efforts invested to resolve them and promote long-term care in stroke cases.